PP.20.01: THE INFLUENCE OF ANTIHYPERTENSIVE TREATMENT ON ARTERIAL STIFFNESS, SHEAR STRESS AND ACTIVITY OF CHOSEN MATRIX METALLOPROTEINASES. (June 2015) - Pizon, T.; Rajzer, M.; Rojek, M.; Czarnecka, D.
Abstract : Objective: Comparison of therapeuthic effects of chosen antihypertensive drugs on arterial stiffness, shear stress in carotid arteries and metalloproteinases activity, moreover analysis of relationship of these variables in the course of treatment. Design and method: 95 never treated patients with HT stage 1 or 2 were randomized to 6 months monotherapy with: quinapril, amlodipine, hydrochlorothiazide, losartan or bisoprolol. Each therapeuthic group consisted of 19 patients (N = 19). Before and then after 1, 3 and 6 months of treatment carotid-femoral pulse wave velocity (PWV) by using a Complior device, ultrasound of carotid arteries were performed. Blood samples for the measurement of whole blood viscosity were taken during each visit. Shear stress (SS) was calculated on the basis of Irace formula. Serum concentration of metalloproteinase 3 (MMP-3) and plasma concentration of tissue inhibitor of metalloproteinase 1 (TIMP-1) were measured at the initial visit and after 6 months of treatment. Results: ANOVA for repeated measurements revealed for all groups significant decrease of PWV and MMP-3 concentration and increase of shear stress in carotid artery and TIMP-1 concentration (p < 0.05). No between groups differences appeared in above effects (p > 0.05). Conclusions: Irrespectively of chosen drug we observed similar effect for PWV drop. Reduction of arterial stiffness as a result of antihypertensive therapy is strongly connected with shear stress increase that is secondary to blood flow velocity growth and changes in connective tissue metabolism.